Depression and Anxiety in Patients With Cancer: A Cross-Sectional Study - Naser, Abdallah Y.; Hameed, Anas Nawfal; Mustafa, Nour; Alwafi, Hassan; Dahmash, Eman Zmaily; Alyami, Hamad S.; Khalil, Haya (Frontiers in Psychology, 2021)
Objectives: Depression and anxiety persist in cancer patients, creating an additional burden during treatment and making it more challenging in terms of management and control. Studies on the prevalence of depression and anxiety among cancer patients in the Middle East are limited and include many limitations such as small sample size and being restricted to a specific type of cancer in specific clinical settings. This study aimed to describe the prevalence and risk factors of depression and anxiety among cancer patients. Material and Methods: A total of 1,011 patients formed the study sample. Patients’ psychological status was assessed using the Hospital Anxiety and Depression Scale (HADS), the Patient Health Questionnaire (PHQ-9), and the Generalised Anxiety Disorder 7-item (GAD-7) scale. The prevalence rate of depressive and anxious symptomatology was estimated by dividing the number of patients who exceeded the borderline score: ten or more for each subscale of the HADS scale, 15 or more for the GAD-7 scale, and 15 or more in the PHQ-9 by the total number of the patients. Results: The prevalence of depressive and anxious symptomatology was 23.4% and 19.1–19.9%, respectively. Depressive symptomatology was more prevalent across patients who were hospitalised (37.1%) compared to patients in the outpatient setting (14.5%) (p<0.001). Similarly, anxious symptomatology was more prevalent across the inpatient setting (p<0.001). In the inpatient setting, depressive symptomatology was more prevalent among patients with bladder cancer, while severe anxious symptomatology was more prevalent across patients with lung cancer. In the outpatient setting, depressive and anxious symptomatology were more prevalent among breast and prostate cancer patients, respectively. Despite that, around 42.7% and 24.8% of the patients, respectively, self-reported that they feel anxious and depressed, and only 15.5% of them were using medications to manage their conditions. Conclusion: Our study findings demonstrated a higher prevalence of depressive and anxious symptomatology in the inpatient setting and advanced disease stages. In addition, the underutilisation of antidepressant therapy was observed. There is a need to consider mental disorders as part of the treatment protocol for cancer patients. Enhanced clinical monitoring and treatment of depression and anxiety among cancer patients are required.